Responsible innovation in human germline gene editing: Background document to the recommendations of ESHG and ESHRE - De Wert, Guido (Eur J Hum Genet, 2018)
Technological developments in gene editing raise high expectations for clinical applications, including editing of the germline. The European Society of Human Reproduction and Embryology (ESHRE) and the European Society of Human Genetics (ESHG) together developed a Background document and Recommendations to inform and stimulate ongoing societal debates. This document provides the background to the Recommendations. Germline gene editing is currently not allowed in many countries. This makes clinical applications in these countries impossible now, even if germline gene editing would become safe and effective. What were the arguments behind this legislation, and are they still convincing? If a technique could help to avoid serious genetic disorders, in a safe and effective way, would this be a reason to reconsider earlier standpoints? This Background document summarizes the scientific developments and expectations regarding germline gene editing, legal regulations at the European level, and ethics for three different settings (basic research, preclinical research and clinical applications). In ethical terms, we argue that the deontological objections (e.g., gene editing goes against nature) do not seem convincing while consequentialist objections (e.g., safety for the children thus conceived and following generations) require research, not all of which is allowed in the current legal situation in European countries. Development of this Background document and Recommendations reflects the responsibility to help society understand and debate the full range of possible implications of the new technologies, and to contribute to regulations that are adapted to the dynamics of the field while taking account of ethical considerations and societal concerns.